Scaled flight testing for evaluating distributed electric propulsion - Jentink, H.W.; Döll, C.; Iannelli, P.; Hoogreef, M.; Kierbel, D. (ICAS, 2024)
The potential of Distributed Electric Propulsion (DEP) for future aircraft has been evaluated with Scaled Flight Testing (SFT). Scaled flight testing can contribute to a reduction of risk and cost in the development of a radically new aircraft. The flight dynamics and control of the aircraft have specifically been addressed. The validity of results of scaled flight testing for predicting the full-scale aircraft properties was addressed in a first campaign. A 1:8.5 scaled version of a typical large passenger aircraft was built, tested in the wind tunnel and was subsequently flight tested. During the flight tests an accurate flight test instrumentation system measured the scaled aircraft flight parameters, such as motion, control surface deflections and air data. Results of the scaled flight testing have been compared with full-scale test results which validates the scaled flight testing methodology. In a second campaign the methodology is applied to investigate and demonstrate the benefits of distributed electric propulsion. Aircraft with the same external shape have been used in the two test campaigns, modifying only the propulsion: the twin turbo-jet propulsion of the first campaign was replaced by propulsion with six propellers in the second campaign. This paper presents the highlights and key results of the development, manufacturing, wind tunnel tests, ground tests, taxi tests and flight tests of both campaigns.